Penguatan Daya Saing Daerah Melalui Promosi Kuliner Palito Daun di Kabupaten Kampar, Riau - Gusliana HB; Syaifullah Yophi; Dedi Kusuma Habibie; Sukamarriko Andrikasmi; Ricki Musliadi; Zulwisman Zulwisman; Fahrur Rozi (Unri Conference Series: Community Engagement, 2025)
This community service activity aims to strengthen regional competitiveness by promoting the traditional culinary specialty Palito Daun as a cultural identity and economic potential in Kampar Regency, Riau. Palito Daun culinary delights possess high local wisdom and offer the potential to be developed as a superior regional product. The activity included outreach, branding strategy training, digital-based promotional assistance, and facilitation of business legality for culinary MSMEs. The results demonstrated improved participant skills in more attractive product packaging, utilizing social media for promotion, and understanding the importance of legality in expanding the market. Furthermore, this activity fostered collective community awareness of the importance of preserving traditional recipes while simultaneously developing them to suit modern market tastes. This community service activity is expected to be a strategic step in strengthening Kampar Regency's image as a region with distinctive culinary delights capable of competing locally, nationally, and internationally.